2005
DOI: 10.1200/jco.2005.06.147
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin M Monoclonal Gammopathies of Undetermined Significance and Indolent Waldenström's Macroglobulinemia Recognize the Same Determinants of Evolution Into Symptomatic Lymphoid Disorders: Proposal for a Common Prognostic Scoring System

Abstract: A B S T R A C T PurposeTo evaluate the clinicohematologic variables at diagnosis that are prognostically related to neoplastic progression in patients with immunoglobulin M (IgM) monoclonal gammopathies of undetermined significance (MGUS), and indolent Waldenström's macroglobulinemia (IWM), and propose a scoring system to identify subsets of patients at different risk. Patients and MethodsWe evaluated 217 patients with IgM MGUS and 201 with IWM (male-female ratio, 131:86 and 117:84; mean age, 63.7 and 63.6 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 23 publications
(17 reference statements)
6
48
0
2
Order By: Relevance
“…3 The criteria we use differ 2 and are based on subsequent studies. [12][13][14] We consider asymptomatic patients with an IgM M protein Ͻ 3 g/dL and lymphoplasmacytic infiltration less than 10% as IgM MGUS, and not WM. 2 Because these patients have a survival similar to the general population and require no therapy, they should not be erroneously labeled as having a malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…3 The criteria we use differ 2 and are based on subsequent studies. [12][13][14] We consider asymptomatic patients with an IgM M protein Ͻ 3 g/dL and lymphoplasmacytic infiltration less than 10% as IgM MGUS, and not WM. 2 Because these patients have a survival similar to the general population and require no therapy, they should not be erroneously labeled as having a malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The separation of IgM MGUS from Waldenström macroglobulinemia using the Mayo criteria is validated by studies of the natural history of IgM MGUS that show that patients diagnosed as having this disorder have a survival rate similar to that in the general population. [20][21][22] Recommendation: In practice, IgM monoclonal gammopathy (regardless of the size of the M protein) plus 10% or greater bone marrow lymphoplasmacytic infiltration (usually intertrabecular) by small lymphocytes that exhibit plasmacytoid or plasma cell differentiation and a typical immunophenotype (eg, surface IgM + , CD5¯, CD10¯, CD19 + , CD20 + , CD23¯, CD79a + and PAX5 + ) that satisfactorily excludes other lymphoproliferative disorders, including chronic lymphocytic leukemia and mantle cell lymphoma, is considered diagnostic of Waldenström macroglobulinemia (Table 3). Because no standard exists for the pathologic evaluation of Waldenström macroglobulinemia, the immunophenotyping approach used may vary.…”
Section: Diagnosismentioning
confidence: 99%
“…In contrast to the results of overall survival, the amount of monoclonal protein was the only significant factor associated with a high incidence of requiring treatment for lymphoid malignancies. The study by Baldini et al 7 reported that 6.9% of the 217 patients with IgM MGUS required chemotherapy after a median follow-up of 56.1 months, and 22.4% of the 201 patients with asymptomatic WM required chemotherapy after a median follow-up of 60.2 months. The variables inversely correlated with evolution were the amount of IgM monoclonal protein, the hemoglobin level, and gender (male or female).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as bone marrow examination was not performed on most of these patients at the time of IgM monoclonal protein detection, these patients were unable to be separated into IgM MGUS and asymptomatic WM by International myeloma working group. 6 Baldini et al 7 found that both IgM MGUS and asymptomatic WM have the same determinants related to evolution, and devised a scoring system to identify subsets of patients affected by "asymptomatic macroglobulinemias" integrated from IgM MGUS and asymptomatic WM. We considered the 63 patients to have "asymptomatic IgM monoclonal gammopathy", which consists of IgM MGUS and asymptomatic WM, and analyzed the overall survival and cumulative incidence of requiring treatment.…”
Section: Discussionmentioning
confidence: 99%